Supplementation with sweet corn for weight gain in pregnant women - Mudlikah, Siti; Nadhiroh, A`im Matun; Wiliyanarti, Pipit Festi (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
Background: Inadequate nutrient intake during pregnancy can cause insufficient weight gain, chronic energy shortage, and difficulties for both the mother and the baby. This study highlights the benefits of sweet corn supplementation in improving weight gain and nutritional condition for pregnant women, addressing nutrient deficiencies and chronic energy shortages. Purpose: This study aims to determine the effect of sweet corn supplementation on increasing body weight in pregnant women. Method: The study employed a pre-experimental one-group pre-test-posttest design. Conducted in August 2024 at Posyandu in Jatikalang Village, it involved 18 pregnant women in their second and third trimesters who had not gained weight, with 15 selected purposively. Data analysis included a T-test statistical approach and the Subjective, Objective, Assessment, and Plan (SOAP) method for each participant. Results: The results showed that the average weight of pregnant women before the intervention was 63.87 kg; the average weight increased to 67.33 kg after the intervention (p<0.05). SOAP analysis found that after eating sweet corn, 67% of pregnant women obtained balanced nutrition, 60% gained weight, and the number of pregnant women with chronic energy deficit (CED) decreased from two to one (7%). In addition, 73% of pregnant women had a favorable opinion. Conclusion: The study suggests that sweet corn supplementation improves pregnant women's weight gain and overall nutritional condition.